A gestão da manutenção e a TPM: uma abordagem visando as melhores práticas de manutenção - Silva, Elaine Cristina Xavier da (2012)
The management and implementation of best practices for effective management of maintenance in production systems, still are important objects of study for managers in this area. It is necessary to work with planning and the use of work philosophies designed to better production performance with a focus on quality. This work addresses the Maintenance Management and its related management techniques, indicates the characteristics of the main types of maintenance, Total Productive Maintenance steps and factors framed for maintenance practices. Aiming to analyze the types of maintenance from the perspective of Total Productive Maintenance and its better applicability in the industrial sector, presents bibliographically; concepts of failures and losses in the process, on the pillars of Total Productive Maintenance and Maintenance. Will be addressed in this monograph management of maintenance processes, in terms of Total Productive Maintenance. In conclusion TPM in their overall development, maintenance management to assist on technical improvement and building a cohesive and efficient environment with respect to the strategic role of maintenance within companies. It can also be concluded that the management of maintenance, total productive maintenance plays a major role in organizing the activities of the sector.